-5(t-2)-(t+2)=3

Simple and best practice solution for -5(t-2)-(t+2)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(t-2)-(t+2)=3 equation:


Simplifying
-5(t + -2) + -1(t + 2) = 3

Reorder the terms:
-5(-2 + t) + -1(t + 2) = 3
(-2 * -5 + t * -5) + -1(t + 2) = 3
(10 + -5t) + -1(t + 2) = 3

Reorder the terms:
10 + -5t + -1(2 + t) = 3
10 + -5t + (2 * -1 + t * -1) = 3
10 + -5t + (-2 + -1t) = 3

Reorder the terms:
10 + -2 + -5t + -1t = 3

Combine like terms: 10 + -2 = 8
8 + -5t + -1t = 3

Combine like terms: -5t + -1t = -6t
8 + -6t = 3

Solving
8 + -6t = 3

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + -6t = 3 + -8

Combine like terms: 8 + -8 = 0
0 + -6t = 3 + -8
-6t = 3 + -8

Combine like terms: 3 + -8 = -5
-6t = -5

Divide each side by '-6'.
t = 0.8333333333

Simplifying
t = 0.8333333333

See similar equations:

| 3a-2=5a-18 | | 5(2s+15)=10(s+1)-12s | | M=2TH+2TA | | 10(2+x)+5=2 | | 10(2+x)+5=0 | | 10(2+x)+0=5 | | 7x4/6 | | 5+8(x-5)=2-2(x-2) | | 10m+70=10m+10-16m | | 10(2+x)+0=6 | | -3(r+2)=-15 | | 2w+10=60 | | 2n+1+n=-8 | | W/5=24-4 | | X-13-2x=2 | | 2x^3+12x^2+16x=y | | 18p+q+3p+12q= | | x+78=72 | | 3(5x-8)-6x+20=-22 | | X+99=93 | | 4(3r-4)=3(r+9)+2 | | b-1/2=2 | | 3(Y+9)+3Y=30 | | 10+6a=-104 | | f(x)=3x^2+5x+7 | | X/2-430 | | 2(t+8)=8 | | 9x-6=7y+3x | | 5y+6q=20 | | 200+.62x=379.8 | | 4x^2-10x-126=0 | | 2x-x=-1+3 |

Equations solver categories